Shane J. Wood, The Alter-Imperial Paradigm. Empire Studies and the Book of Revelation (Biblical Interpretation Series 140; Leiden – Boston: Brill 2016) - Bergel, Łukasz (The Biblical Annals, 2017)
Book review: Shane J. Wood, The Alter-Imperial Paradigm. Empire Studies & the Book of Revelation (Biblical Interpretation Series 140; Leiden – Boston: Brill 2016). Pp. XIV + 300. € 115. ISBN 978-9004-30802-2 (hardcover).